Majorana-like end states in one-dimensional dimerized Kitaev topolectrical circuit - Junjie Yao; Xiamin Hao; Biyu Song; Yizhen Jia; Chenqiang Hua; Miao Zhou (New Journal of Physics, 2022)
Majorana zero modes (MZMs) have attracted tremendous attention in condensed matter and materials physics communities due to the implications in topological quantum computation. One-dimensional (1D) dimerized Kitaev chain is a prototype model for MZMs, but its realization remains a challenge in material systems. Here, we develop a distinctive approach to achieve Majorana-like end states (MESs) by implementing practical dimerized Kitaev topolectrical circuits. Specifically, two arrays of inductors are arranged to simulate particles and antiparticles, while intra- and inter-array capacitive connections are used to model hopping and superconducting pairing. Three topological phases can be achieved by tuning the capacitance, i.e. the trivial phase, Su–Schrieffer–Heeger topological phase and Kitaev phase, with distinct field strength distributions in real space. Majorana splitting is observed around a domain wall in the circuit, and we propose an efficient experimental observable-edge distance-to characterize the process as premonition of topological phase transition. Remarkably, dynamics of the Gaussian wave packet in time domain provide an excellent signal to detect MESs in experiments, as only MESs allow nonlocal propagation in circuit network. Our results not only manifest the superiorities of topolectrical circuits for exotic topological states, but also pave the way for possible applications in electrical engineering and signal processing.